Tratamento do efluente aquoso da indústria de papel e celulose por coagulação e floculação seguido de fotocatálise com TiO2/H2O2 - Rodrigues, Angela Claudia (2007)
The fresh water is limited in the nature and has been contaminated by the industrial and domestic wastewaters. The cellulose and paper industries are considered one of the largest sources of aquatic pollution by generating a great amount of water containing lignin and theirs compounds, which shows high chemical oxygen demand (COD) and low biodegradability. The aim of the present work was to increase the purification of the coming eflluent from the bleaching process of the cellulose industry using a combination of two treatments. Firstly was investigated the coagulation and flocculation process by ferric chloride and ferric sulfate (separately) as coagulants and the chitosan as auxiliary polyelectrolyte in the coagulation. Secondly, the photocatalysis of the sobrenadant eflluent generated in the first treatment was realized. In the illumination studies were employed lamps of mereury's vapor (3x of 250 W) and the UV/TiO2/H2O2 system. In the coagulation/flocculation, the statistic analysis shows that the ferric chloride was significantly more efficient than the ferric sulfate, and the best experimental conditions for the treatment were: 80.0 mg L-1 of FeCl3, 50.0 mg L-1 of chitosan and pH = 6.0. When the coagulation was performed with FeCl3 alone (pH = 6.0), the reduction of COD and turbidity are 54 and 75 % respectively; also a high inorganic ions removal was observed. The absorbance reduction is 90 % in the visible region and 70 to 80 % for wavelengths corresponding to the aliphatic groups and aromatics rings (254, 280 and 310 nm). With the addition of 50 mg L-1 of chitosan, an increasing inorganic ions removal and a larger reduction of the turbidity (from 75 % to 90 %) were noticed, although no expressive decrease of COD and absorbance were observed. In the photocatalysis treatment, the process optimization was obtained with 0,50 g L-1 of TiO2, 10 mmol L-1 of H2O2 and pH = 3.0. The formation of sol- ions was observed due to the degradation of suspended organic matter. After 6 hours of irradiation the reduction of COD was 81 %. The reduction of the absorbance in the region related to aromatic and conjugated aliphatic groups happened up to 120 min of irradiation, decreasing 94 %; the kinetic profile obeys a first-order reactions law and the t1/2 was smaller than 30 minutes for intensities monitored at wavelengths of aromatic region. For the visible wavelength region the absorption decreased to zero and was very fast, indeed, not allowing obtain reliable numeric results. The toxicity studies employing Artemia salina organisms as bio-assays indicated that after the treatments an expressive decrease of toxic pollutants in the water eflluents, mainly after the process combination. It can be affirmed that the process realized in association and in the sequence using optimized experimental procedures as investigated would provided good results. This fact is reaffirmed by the transparency and absence of colors and odor in the treated water.